The liquidscape of Mare Nostrum: Manoel de Oliveira and Banksy's Mediterranean crossings. Issue 5 (3rd September 2019) - Mendes, Ana Cristina
ABSTRACT: The Mediterranean Sea has never ceased to be of geopolitical strategic importance, but its presence in the mediascape has grown in prominence since 2010, in what has been labelled as the Mediterranean 'crisis'. Drawing on an understanding of the Mediterranean Sea as a discursive space of political, economic and cultural identity conflicts, this article moves excursively from A Talking Picture ( Um Filme Falado ), a 2003 film directed and written by Portuguese filmmaker Manoel de Oliveira, to a composite photograph, unofficially attributed to Banksy, inspired by the refugee crisis in Europe, to examine representations of the postimperial liquidscapes of Mare Nostrum. Guided by these two film and graphic art texts, the article travels from the Mare Nostrum that corresponds to the liquidscapes of European civilization's birth, as suggested by Oliveira's work, to the Mare Nostrum that was the site of an eponymous military and humanitarian operation devised by the Italian government following the 2013 Lampedusa migrant shipwreck. As for the critical framework for scrutinizing these cross-media representations of liquidscapes, this article sets out to revisit Arjun Appadurai's theorization for understanding global cultural flows, proposed almost three decades ago, arguing for the enduring topicality of the imaginary landscapes of scapes.